EXTENSION DURING CONTINENTAL CONVERGENCE, WITH APPLICATION TO THE TIBETAN PLATEAU - England, P; Houseman, G (1989)
The Tibetan plateau is the product of crustal thickening caused by the collision between India and Asia and is the largest active example of extensional tectonics in a zone of continental collision. Throughout most of the Tertiary, the tectonics of the plateau were dominated by north-south shortening, a significant proportion of which took place on east-west striking thrust faults. For the last 5 m.a. or so the plateau has been thinning by the mechanism of extension on north-south trending normal faults. Previous investigations of the collision have been able to account for the large-scale features of the Tertiary deformation but have failed to explain the transition, in the late Tertiary to Quaternary strain rate field of the plateau, from north-south compression to east-west extension. The transition could, in principle, be effected by a reduction in the rate of convergence between India and Asia or by a uniform reduction in strength of the whole continental lithosphere of Asia. Numerical experiments show that for a range of lithospheric parameters, the increase in surface height (as much as 2 km) and of potential energy (5 to 10 × 1012 N m-1) resulting from convective instability of the lower lithosphere are sufficient for east-west extension to replace north-south compression as the dominant feature of the stress field of the Tibetan plateau. -from Authors